2013
DOI: 10.1182/blood-2013-04-493973
|View full text |Cite
|
Sign up to set email alerts
|

Nfix is a novel regulator of murine hematopoietic stem and progenitor cell survival

Abstract: Key Points HSPCs fail to persist in the bone marrow of lethally irradiated recipients in the absence of Nfix. Nfix-deficient HSPCs display increased apoptosis during ex vivo culture and in recipient marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 34 publications
(25 reference statements)
1
64
0
Order By: Relevance
“…In addition, NFIX balances the hematopoietic stem cell (HSPC) survival and apoptosis (Holmfeldt et al, 2013). Functional studies show that NFIX expression is activated by Pax7 in fetal muscles, which activates transcription of fetal specific genes and represses embryonic genes such as slow myosin (Messina et al, 2010;Heng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NFIX balances the hematopoietic stem cell (HSPC) survival and apoptosis (Holmfeldt et al, 2013). Functional studies show that NFIX expression is activated by Pax7 in fetal muscles, which activates transcription of fetal specific genes and represses embryonic genes such as slow myosin (Messina et al, 2010;Heng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a transcriptome-wide approach revealed that Nfia induces an eythroid transcriptional program in both CD34 + and leukaemic K562 cells [6]. Nfix knockout mice die postnatally around p21 and have brain, intestine, and skeleton malformations [7,8] and Nfix deficient HSPCs fail to persist in long-term bone marrow engraftment upon transplantation [9]. Recently Nfix was shown to be one of 36 regulatory factors with relatively restricted expression in HSCs, that contributed towards converting a committed B cell to a myeloid cell [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies employing conditional knockout strategies and/or in vitro models have begun to uncover NFI function in these cellular populations. Intriguingly, these studies suggest that, in adult tissue, NFI factors play a contrasting role to that during development, serving to promote quiescence and/or survival of stem cells, rather than their differentiation (Chang et al, 2013;Holmfeldt et al, 2013;Martynoga et al, 2013). , 1999).…”
Section: Genetic Redundancy Of Nfis During Developmentmentioning
confidence: 99%
“…No increase in transcript levels within HFSCs relative to progeny (Tumbar et al, 2004 (Chang et al, 2013;Holmfeldt et al, 2013;Martynoga et al, 2013 it is a strong possibility that inactivating mutations in Nfi genes will be identified in developmental based cancers. Indeed, as discussed in this review, there are a number of recent studies that have shown a potential role for inactivating mutations in NFIs in driving tumorigenesis in medulloblastoma, the most common childhood brain cancer (Wu et al, 2012;Genovesi et al, 2013;Lastowska et al, 2013).…”
Section: Nfix Promotes Survival Of Hematopoietic Stem and Progenitor mentioning
confidence: 99%
See 1 more Smart Citation